Workload Analysis of Employees in The Reservations Department at Hotel XYZ - Cintya Prameswari; I Gusti Agung Gede Witarsana; Cahyo Purnomo Loanata (Politeknik Sahid, 2026)
This research seeks to evaluate the workload of employees in the Reservations Department at Hotel XYZ by reviewing working conditions, length of working hours, and the achievement of performance targets, as well as identifying the optimal number of staff required. A descriptive qualitative method was applied in this study. Data were gathered through in-depth interviews, direct observation, and document review to gain a comprehensive understanding of task allocation and the intensity of employee workload. The results indicate that employees experience a significantly heavy workload, particularly during peak seasons, leading to extended working hours and frequent overtime. Fluctuating operational demands and high performance expectations contribute to increased work pressure, potentially affecting productivity and service standards. Based on calculations using the Workload Analysis approach, staffing for the Reservation Manager and Supervisor positions is considered sufficient. However, there is a shortage of two Reservation Agents, which creates excessive responsibilities at the operational level. The analysis is based on 234 effective working days annually and a 40-hour workweek. After accounting for a 30% allowance for non-productive time, the effective working time is 28 hours or 1,680 minutes per week, forming the basis for staffing estimation. These findings emphasize the importance of adjusting workforce allocation, conducting periodic evaluations, offering time management training, and adopting automation systems to enhance operational efficiency. This study’s contribution lies in combining qualitative insights with quantitative workload measurement to support strategic human resource planning in hospitality settings affected by seasonal fluctuations.